Assessing the total theoretical, and financially viable, resource of biomethane for injection to a natural gas network in a region. (15th February 2017) - O'Shea, Richard; Wall, David M.; Kilgallon, Ian; Browne, James D.; Murphy, Jerry D.
Highlights: The total theoretical biomethane resource of grass silage in a region was estimated. A theoretical biomethane resource of ca. 138 PJ was identified. An optimisation model determined profitable biomethane facility locations. Profitable plants produced 12 PJ of biomethane, 8.6% of the theoretical resource. Approximately 22% of industrial gas demand could be supplied by profitable plants. Abstract: The total theoretical biomethane resource of cattle slurry and grass silage in Ireland was estimated using the most up to date spatially explicit data available. The cattle slurry resource (9.6 PJ) was predominantly found in southern and north-eastern regions while the grass silage resource (128.4 PJ) was more concentrated in western regions. The total biomethane resource of cattle slurry and grass silage was equivalent to 6% and 76% of total natural gas consumption in Ireland in 2014/15, respectively. A sequential optimisation model was run to determine where to source cattle slurry and grass silage from, for 42 potential biomethane plant locations in Ireland. The concept was to maximise plant net present value (NPV) and develop locations in order of plant profitability. The impact of plant size, grass silage price, volatile solids ratio (VSR) of grass silage to cattle slurry, and incentive per unit energy of biomethane was assessed in 81 separate scenarios. The results indicated that total biomethane production from plants with a positive NPV ranged from 3.51 PJ/a to 12.19 PJ/a, considerably less than the total resource. The levelised cost of energy (LCOE) of plants was also calculated and ranged from ca. 50.2 €/MW h to ca. 109 €/MW h depending on the various plant parameters. LCOE decreased with increased plant size and ratio of grass silage to cattle slurry. The relationship between grass silage price and LCOE was assessed. In the median scenario (33 €/twwt grass silage, VSR of 4, 75, 000 twwt /a plant size, 60 €/MW h incentive) cattle slurry was sourced within 6.4 km of the facility while grass silage was sourced within 10.5 km of the facility. A high level assessment of the carbon dioxide intensity of biomethane from the median scenario was conducted and showed a potential greenhouse gas reduction of 74–79% when compared to natural gas.